Pengaruh Gaya Kepemimpinan Demokrasi dan Komitmen Organisasi terhadap Kinerja Pegawai dengan Empowerment sebagai Variabel Intervening di Kantor Imigrasi Kelas I TPI Padang - Syarah, Annisa; Sari, Marta Widian; Sari, Yosi Puspita (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study aims to examine the effect of democratic leadership style and organizational commitment on employee performance with empowerment as an intervening variable at the Class I Immigration Office (Kantor Imigrasi Kelas I TPI) in Padang. The data collection method in this study was to use a questionnaire with a sample size of 75 respondents. Data analysis in this study used SmartPLS V3.0 with the SEM (structural equation modeling) analysis method. The results showed that (a) there is an insignificant positive effect of democratic leadership style on empowerment. (b) there is a significant positive effect of organizational commitment on empowerment. (c) there is an insignificant positive effect of democratic leadership style on employee performance. (d) there is a significant positive effect of organizational commitment on employee performance. (e) there is a significant positive effect of empowerment on employee performance. (f) there is an insignificant positive effect of democratic leadership style on employee performance through empowerment. (g) there is a significant positive effect of organizational commitment on employee performance through empowerment.